Application of resequencing microarrays in microbial detection and characterization. (May 2012) - Leski, Tomasz A; Lin, Baochuan; Malanoski, Anthony P; Stenger, David A
Microarrays are powerful, highly parallel assays that are transforming microbiological diagnostics and research. The adaptation of microarray-based resequencing technology for microbial detection and characterization resulted in the development of a number assays that have unique advantages over other existing technologies. This technological platform seems to be especially useful for sensitive and high-resolution multiplexed diagnostics for clinical syndromes with similar symptoms, screening environmental samples for biothreat agents, as well as genotyping and whole-genome analysis of single pathogens.